High-elasticity breathable fabric and preparation method thereof

By spinning fluorinated polymer with modified nanotitanium dioxide and blending it with cotton and nylon, a highly elastic breathable fabric was prepared, which solved the problem of functional degradation of existing fabrics after long-term use, and achieved versatility and long-term functional maintenance.

CN119615465APending Publication Date: 2025-03-14GUANGZHOU GUANYU WEAVING CO LTD

Patent Information

Application Number
CN202411510245.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing high elastic breathable fabrics are prone to peel off the layered structure and deteriorate their functions after long-term use, and cannot maintain their functional effects for a long time.

Method used

Fluorinated fibers were obtained by spinning the fluorinated polymer with modified nanotitanium dioxide and combined with cotton and nylon by blending the fluorinated polymer to prepare a highly elastic breathable fabric.

Benefits of technology

It realizes the high elasticity and breathability of the fabric, while effectively increasing antibacterial, ultraviolet resistance, waterproofness and stain resistance, extending the functional maintenance time of the fabric.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005105257690000071
    Figure BDA0005105257690000071
Patent Text Reader

Abstract

The invention discloses a high-elasticity breathable fabric and a preparation method thereof, and relates to the technical field of fabrics. The preparation method comprises the following steps: firstly, carrying out esterification reaction on fluorinated dihydric alcohol and terephthalic acid to obtain a fluorinated polymer, then carrying out coating modification on nano titanium dioxide by using chitosan to obtain modified nano titanium dioxide with microsphere morphology, adding the modified nano titanium dioxide as a new filler into a molten fluorine-containing polymer, and carrying out electrostatic spinning operation to obtain the modified nano titanium dioxide / fluorine-containing polymer composite material. The preparation method comprises the following steps: preparing a fiber material with a high specific surface area, and carrying out two-for-one twisting, spinning, weaving and other operations on the obtained fiber to finally prepare the high-elasticity breathable fabric. The high-elasticity breathable fabric prepared by the invention has long-acting antibacterial, anti-ultraviolet, water-resistant and stain-resistant effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fabrics, in particular to a highly elastic breathable fabric and a preparation method thereof. Background Art

[0002] With the advancement of science and technology, people's living standards are constantly improving, and the quality requirements for daily necessities in life are also constantly improving. In particular, the pursuit of clothing fabrics is gradually updated, requiring fabrics to have various functions. High elasticity and breathable fabrics are a kind of fabric that combines high elasticity and good breathability. This kind of fabric has broad application prospects in many fields. While achieving high elasticity and breathability, people also hope that the fabric has more functions, such as antibacterial, waterproof and anti-fouling, anti-ultraviolet and so on. At present, most fabrics can only achieve two or three of them, and most of them are designed as layered composite fabrics, or the existing fabrics are functionally sprayed, impregnated and other methods to achieve the special functions of the fabric. This kind of fabric may cause the layered structure to peel off due to wear and tear after long-term use, resulting in the degradation of the final fabric function, and it is impossible to maintain the functional effect for a long time. Summary of the invention

[0003] The object of the present invention is to provide a highly elastic breathable fabric and a preparation method thereof, so as to solve the problems existing in the prior art.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a highly elastic breathable fabric, wherein the highly elastic breathable fabric is prepared by spinning a fluorinated polymer and modified nano titanium dioxide to obtain fluorinated fibers, and finally by a blending process.

[0005] Furthermore, the fluorinated polymer is prepared by esterification reaction of 2,2-difluoro-1,3-propylene glycol and terephthalic acid.

[0006] Furthermore, the modified nano titanium dioxide is prepared by coating and modifying nano titanium dioxide with chitosan.

[0007] Furthermore, the blending process uses fluorinated fibers, cotton, and nylon.

[0008] Furthermore, a method for preparing a highly elastic breathable fabric comprises the following preparation steps:

[0009] (1) Add terephthalic acid, 2,2-difluoro-1,3-propanediol, and tetrabutyltitanium bromide to dimethyl sulfoxide, place in a reaction kettle, stir at 30-40° C., 50-150 r / min for 0.5-2 h, transfer the reactants into a reaction kettle, stir at 0.08-0.12 MPa, 200-250° C., nitrogen atmosphere, at a stirring rate of 100-200 r / min, continue stirring for 1-4 h, continue pressurizing and heating, finally stir at 0.2-0.5 MPa, 250-270° C., at a stirring rate of 150-300 r / min for 3-6 h, cool and reduce the pressure to room temperature and pressure in a nitrogen atmosphere, and prepare a fluorinated polymer;

[0010] (2) adding nano titanium dioxide with a particle size of 50 to 100 nm to distilled water, ultrasonically dispersing at a frequency of 50 to 200 kHz for 20 to 50 min to obtain solution A, stirring at a rate of 100 to 400 r / min at 30 to 50° C., adding chitosan while stirring, and continuing stirring for 30 to 60 min to obtain solution B, stirring at a rate of 200 to 400 r / min at 60 to 120° C. under a nitrogen atmosphere for 1 to 2 h, adding propylene oxide while stirring, reacting in a water bath at 60 to 80° C. for 4 to 8 h, cooling to room temperature after the reaction is completed, centrifuging at 4000 to 7000 rpm for 10 to 50 min, filtering to obtain a solid, drying at 50 to 80° C. for 2 to 4 h, and grinding the product to 100 to 200 meshes to obtain modified nano titanium dioxide;

[0011] (3) drying the fluorinated polymer in a vacuum of 0.001 to 0.003 MPa at 100 to 150° C. for 4 to 8 hours, adding modified nano-titanium dioxide to the dried fluorinated polymer, and extruding the molten liquid through a nozzle with a nozzle aperture of 0.5 to 1.5 mm under high temperature, high voltage and nitrogen atmosphere to prepare a fluorinated high-elastic fiber;

[0012] (4) 100-200 parts of fluorinated high elastic fiber, 300-600 parts of cotton and 200-400 parts of nylon are twisted, spun and woven to obtain a 200-400 g / m2 2 Highly elastic and breathable fluorinated polyester fabric.

[0013] Furthermore, in the step (1), the mass ratio of dimethyl sulfoxide, terephthalic acid, 2,2-difluoro-1,3-propylene glycol and tetrabutyltitanium bromide is 70-150:50-80:20-40:0.5-2.

[0014] Furthermore, the mass ratio of distilled water, nano-titanium dioxide, chitosan and propylene oxide in step (2) is 50-100:5-10:15-30:1-5.

[0015] Furthermore, in the step (3), the mass ratio of the fluorinated polymer to the modified nano-titanium dioxide is 10-20:5-10.

[0016] Furthermore, the high temperature in step (3) is 250-300°C.

[0017] Furthermore, the high voltage in step (3) is 20 to 50 kV.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0019] The high elasticity and breathable fabric prepared by the present invention not only realizes high elasticity and breathability, but also effectively increases the antibacterial property, UV resistance, waterproofness and antifouling property of the fabric.

[0020] Firstly, a fluorinated diol is used to carry out an esterification reaction with terephthalic acid to obtain a fluorinated polymer. Since a carbon-fluorine bond is introduced into the soft segment of the polymer to form a fluorinated segment, the fluorinated segment has a lower surface energy and exhibits excellent water and oil resistance, so it can effectively improve the waterproof and anti-fouling effect of the fiber material. Then, the modified nano titanium dioxide is added to the molten fluorinated polymer as a new filler. Through the spinning operation, the prepared fiber material has a higher specific surface area, and the formed fibers are straight, with a high porosity and excellent water permeability and air permeability. Finally, a suitable textile material is prepared, and a fabric with high elasticity and breathability, antibacterial, sun-proof, waterproof and antifouling properties is obtained.

[0021] Secondly, chitosan is used to coat and modify nano-titanium dioxide. Chitosan is a cationic polymer, while nano-titanium dioxide usually has a negative charge on the surface. The two interact with each other to form a polyelectrolyte complex, and there is a tendency to self-assemble to form core-shell nanospheres. A cross-linking agent is further added, and the chitosan polymer chains are cross-linked under the action of the cross-linking agent to form a coating layer, which is wrapped around the surface of titanium dioxide. The microspheres are dispersed in the melt of fluoropolymer. The microsphere structure makes titanium dioxide have better dispersibility in the melt. The active hydroxyl groups suspended on the outside of the microspheres form hydrogen bonds with the hydrogen in the fluoropolymer, so that the microspheres can better combine with the fibers. On this basis, the surface coating has a better protective effect on the nano-titanium dioxide, allowing it to stay in the fabric for a longer time, extending the anti-ultraviolet effect of the fabric. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the highly elastic breathable fabrics prepared in the following examples are as follows:

[0024] Air permeability: According to the standard GB / T 5453-1997, the air permeability of the high elastic breathable fabrics prepared in Examples 1-3 and Comparative Examples 1-3 was tested using a fully automatic air permeability tester at a temperature of 20°C and a relative humidity of 65%.

[0025] Antibacterial property: According to the standard GB / T 39104.2-2020, the antibacterial value test was performed on the high elastic breathable fabrics prepared in Examples 1-3 and Comparative Examples 1-3;

[0026] High elasticity: According to standard FZ / T70006-2004, the high elastic breathable fabrics prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to tensile elasticity tests using an electronic fabric strength tester;

[0027] Antifouling property: According to the test method described in the national standard GB / T 30159.1-2013, the antifouling property of the high elastic breathable fabrics prepared in Examples 1-3 and Comparative Examples 1-3 was tested;

[0028] Anti-ultraviolet property: According to the test method described in the national standard GB / T 18830-2009, the anti-ultraviolet property of the high elastic breathable fabrics prepared in Examples 1-3 and Comparative Examples 1-3 was tested.

[0029] Example 1

[0030] (1) Add 50 parts of terephthalic acid, 20 parts of 2,2-difluoro-1,3-propylene glycol, and 0.5 parts of tetrabutyltitanium bromide to 100 parts of dimethyl sulfoxide, place in a reaction kettle, stir at 35° C. and 100 r / min for 2 hours, transfer the reactants into a reaction kettle, stir at 0.1 MPa and nitrogen atmosphere at a stirring rate of 150 r / min for 3 hours, continue to pressurize and heat, and finally stir at 0.4 MPa and 260° C. at a stirring rate of 200 r / min for 5 hours, cool and reduce the pressure to room temperature and pressure under a nitrogen atmosphere to obtain a fluorinated polymer;

[0031] (2) Add 5 parts of nano titanium dioxide with a particle size of 80 nm to 100 parts of distilled water, ultrasonically disperse at a frequency of 150 kHz for 40 min to obtain solution A, stir at a rate of 300 r / min at 40°C, add 15 parts of chitosan while stirring, and continue stirring for 60 min to obtain solution B, stir at a rate of 350 r / min at 90°C for 2 h under a nitrogen atmosphere, add 1 part of propylene oxide while stirring, react in a water bath at 70°C for 6 h, cool to room temperature after the reaction is completed, centrifuge at 5000 rpm for 20 min, filter and obtain the solid, dry at 60°C for 3 h, and grind the product to 150 mesh to obtain modified nano titanium dioxide;

[0032] (3) drying 10 parts of fluorinated polymer at 120° C. in a vacuum of 0.003 MPa for 6 h, adding 5 parts of modified nano-titanium dioxide to the dried fluorinated polymer, and extruding the melt through a nozzle with a nozzle aperture of 1 mm at 270° C. and 16 kV in a nitrogen atmosphere to prepare a fluorinated high-elastic fiber;

[0033] (4) 150 parts of fluorinated high elastic fiber, 400 parts of cotton and 300 parts of nylon are twisted, spun and woven to obtain a 300 g / m 2 Highly elastic and breathable fluorinated polyester fabric.

[0034] Example 2

[0035] (1) Add 65 parts of terephthalic acid, 30 parts of 2,2-difluoro-1,3-propylene glycol, and 1.5 parts of tetrabutyltitanium bromide to 100 parts of dimethyl sulfoxide, place in a reactor, stir at 35° C. and 100 r / min for 2 hours, transfer the reactants into a reactor, stir at 0.1 MPa and nitrogen atmosphere at a stirring rate of 150 r / min for 3 hours, continue to pressurize and heat, and finally stir at 0.4 MPa and 260° C. at a stirring rate of 200 r / min for 5 hours, cool and reduce the pressure to room temperature and pressure under a nitrogen atmosphere to obtain a fluorinated polymer;

[0036] (2) Add 7 parts of nano titanium dioxide with a particle size of 80 nm to 100 parts of distilled water, ultrasonically disperse at a frequency of 150 kHz for 40 min to obtain solution A, stir at a rate of 300 r / min at 40°C, add 20 parts of chitosan while stirring, and continue stirring for 60 min to obtain solution B, stir at a rate of 350 r / min at 90°C for 2 h under a nitrogen atmosphere, add 3 parts of propylene oxide while stirring, react in a water bath at 70°C for 6 h, cool to room temperature after the reaction is completed, centrifuge at 5000 rpm for 20 min, filter and obtain the solid, dry at 60°C for 3 h, and grind the product to 150 mesh to obtain modified nano titanium dioxide;

[0037] (3) drying 15 parts of fluorinated polymer at 120° C. in a vacuum of 0.003 MPa for 6 h, adding 7 parts of modified nano-titanium dioxide to the dried fluorinated polymer, and extruding the melt through a nozzle with a nozzle aperture of 1 mm at 270° C. and 16 kV in a nitrogen atmosphere to prepare a fluorinated high-elastic fiber;

[0038] (4) 150 parts of fluorinated high elastic fiber, 400 parts of cotton and 300 parts of nylon are twisted, spun and woven to obtain a 300 g / m 2 Highly elastic and breathable fluorinated polyester fabric.

[0039] Example 3

[0040] (1) Add 80 parts of terephthalic acid, 40 parts of 2,2-difluoro-1,3-propylene glycol, and 2 parts of tetrabutyltitanium bromide to 100 parts of dimethyl sulfoxide, place in a reactor, stir at 35° C. and 100 r / min for 2 hours, transfer the reactants into a reactor, stir at 0.1 MPa and nitrogen atmosphere at a stirring rate of 150 r / min for 3 hours, continue to pressurize and heat, and finally stir at 0.4 MPa and 260° C. at a stirring rate of 200 r / min for 5 hours, cool and reduce the pressure to room temperature and pressure under a nitrogen atmosphere to obtain a fluorinated polymer;

[0041] (2) Add 10 parts of nano titanium dioxide with a particle size of 80 nm to 100 parts of distilled water, ultrasonically disperse at a frequency of 150 kHz for 40 min to obtain solution A, stir at a rate of 300 r / min at 40°C, add 30 parts of chitosan while stirring, and continue stirring for 60 min to obtain solution B, stir at a rate of 350 r / min at 90°C for 2 h under a nitrogen atmosphere, add 5 parts of propylene oxide while stirring, react in a water bath at 70°C for 6 h, cool to room temperature after the reaction is completed, centrifuge at 5000 rpm for 20 min, filter and obtain the solid, dry at 60°C for 3 h, and grind the product to 150 mesh to obtain modified nano titanium dioxide;

[0042] (3) drying 20 parts of fluorinated polymer at 120° C. in a vacuum of 0.003 MPa for 6 h, adding 10 parts of modified nano-titanium dioxide to the dried fluorinated polymer, and extruding the melt through a nozzle with a nozzle aperture of 1 mm at 270° C. and 16 kV in a nitrogen atmosphere to prepare a fluorinated high-elastic fiber;

[0043] (4) 150 parts of fluorinated high elastic fiber, 400 parts of cotton and 300 parts of nylon are twisted, spun and woven to obtain a 300 g / m 2 Highly elastic and breathable fluorinated polyester fabric.

[0044] Comparative Example 1

[0045] (1) Add 65 parts of terephthalic acid, 30 parts of propylene glycol, and 1.5 parts of tetrabutyltitanium bromide to 100 parts of dimethyl sulfoxide, place in a reactor, stir at 35°C and 100 r / min for 2 hours, transfer the reactants into a reactor, stir at 0.1 MPa, nitrogen atmosphere, at a stirring rate of 150 r / min for 3 hours, continue to pressurize and heat, and finally stir at 0.4 MPa, 260°C, at a stirring rate of 200 r / min for 5 hours, cool and reduce the pressure to room temperature and pressure under a nitrogen atmosphere to obtain a polymer;

[0046] (2) Add 7 parts of nano titanium dioxide with a particle size of 80 nm to 100 parts of distilled water, ultrasonically disperse at a frequency of 150 kHz for 40 min to obtain solution A, stir at a rate of 300 r / min at 40°C, add 20 parts of chitosan while stirring, and continue stirring for 60 min to obtain solution B, stir at a rate of 350 r / min at 90°C for 2 h under a nitrogen atmosphere, add 3 parts of propylene oxide while stirring, react in a water bath at 70°C for 6 h, cool to room temperature after the reaction is completed, centrifuge at 5000 rpm for 20 min, filter and obtain the solid, dry at 60°C for 3 h, and grind the product to 150 mesh to obtain modified nano titanium dioxide;

[0047] (3) drying 15 parts of the polymer at 0.003 MPa vacuum at 120° C. for 6 h, adding 7 parts of modified nano-titanium dioxide to the dried polymer, and extruding the melt through a nozzle with a nozzle aperture of 1 mm at 270° C. and 16 kV in a nitrogen atmosphere to prepare a fluorinated high-elastic fiber;

[0048] (4) 150 parts of high-elastic fiber, 400 parts of cotton and 300 parts of nylon are twisted, spun and woven to obtain a 300 g / m 2 Highly elastic and breathable fluorinated polyester fabric.

[0049] Comparative Example 2

[0050] (1) Add 65 parts of terephthalic acid, 30 parts of 2,2-difluoro-1,3-propylene glycol, and 1.5 parts of tetrabutyltitanium bromide to 100 parts of dimethyl sulfoxide, place in a reactor, stir at 35° C. and 100 r / min for 2 hours, transfer the reactants into a reactor, stir at 0.1 MPa and nitrogen atmosphere at a stirring rate of 150 r / min for 3 hours, continue to pressurize and heat, and finally stir at 0.4 MPa and 260° C. at a stirring rate of 200 r / min for 5 hours, cool and reduce the pressure to room temperature and pressure under a nitrogen atmosphere to obtain a fluorinated polymer;

[0051] (2) Add 20 parts of chitosan to 100 parts of distilled water, continue stirring for 60 minutes to obtain solution B, stir at 90°C and 350 r / min for 2 hours under a nitrogen atmosphere, add 3 parts of propylene oxide while stirring, react in a water bath at 70°C for 6 hours, cool to room temperature after the reaction is completed, centrifuge at 5000 rpm for 20 minutes, filter and obtain the solid, dry at 60°C for 3 hours, and grind the product to 150 mesh to obtain spherical chitosan;

[0052] (3) drying 15 parts of fluorinated polymer at 120° C. in a vacuum of 0.003 MPa for 6 h, adding 7 parts of spherical chitosan to the dried fluorinated polymer, and extruding the melt through a nozzle with a nozzle aperture of 1 mm at 270° C. and 16 kV in a nitrogen atmosphere to prepare a fluorinated high-elastic fiber;

[0053] (4) 150 parts of fluorinated high elastic fiber, 400 parts of cotton and 300 parts of nylon are twisted, spun and woven to obtain a 300 g / m 2 Highly elastic and breathable fluorinated polyester fabric.

[0054] Comparative Example 3

[0055] (1) Add 65 parts of terephthalic acid, 30 parts of 2,2-difluoro-1,3-propylene glycol, and 1.5 parts of tetrabutyltitanium bromide to 100 parts of dimethyl sulfoxide, place in a reactor, stir at 35° C. and 100 r / min for 2 hours, transfer the reactants into a reactor, stir at 0.1 MPa and nitrogen atmosphere at a stirring rate of 150 r / min for 3 hours, continue to pressurize and heat, and finally stir at 0.4 MPa and 260° C. at a stirring rate of 200 r / min for 5 hours, cool and reduce the pressure to room temperature and pressure under a nitrogen atmosphere to obtain a fluorinated polymer;

[0056] (2) drying 15 parts of fluorinated polymer at 120° C. in a vacuum of 0.003 MPa for 6 h, adding 7 parts of nano-titanium dioxide with a particle size of 80 nm to the dried fluorinated polymer, and extruding the melt through a nozzle with a nozzle aperture of 1 mm at 270° C. and 16 kV in a nitrogen atmosphere to prepare a fluorinated high-elastic fiber;

[0057] (3) 150 parts of fluorinated high elastic fiber, 400 parts of cotton and 300 parts of nylon are twisted, spun and woven to obtain a 300 g / m 2 Highly elastic and breathable fluorinated polyester fabric.

[0058] Effect example

[0059] Table 1 below shows the performance analysis results of air permeability, antibacterial property, tensile elasticity, antifouling property and UV resistance of Examples 1 to 3 of the present invention and Comparative Examples 1 to 3.

[0060] Table 1 Air permeability, antibacterial value, recovery rate, antifouling results and anti-ultraviolet results of high elastic breathable fabrics prepared in Examples 1 to 3 and Comparative Examples 1 to 3

[0061]

[0062] From the results of Table 1, we found that firstly, terephthalic acid was polymerized with fluorinated propane or propane, and the generated fiber had a high elastic and breathable effect. From the results of the antibacterial value, we found that the use of chitosan can effectively improve the antibacterial property of the fabric. From the anti-fouling effect, the fabric prepared by the reaction of fluorinated propane with terephthalic acid had a better anti-fouling effect than the fabric prepared by the reaction of propane with terephthalic acid. This was mainly caused by the carbon-fluorine bond in the soft segment having a lower surface energy. The carbon-fluorine bond showed a higher hydrophobicity and oleophobicity, which enhanced the waterproof and antifouling effect of the fabric. From the anti-ultraviolet performance test results, it can be seen that the addition of nano-titanium dioxide can effectively improve the anti-ultraviolet performance of the fabric. From the anti-ultraviolet results of Example 2, Comparative Example 2 and Comparative Example 3, we found that chitosan also had a certain influence on the anti-ultraviolet effect of nano-titanium dioxide. The main reason was that chitosan effectively coated nano-titanium dioxide, greatly improved the dispersibility of nano-titanium dioxide in the melt, formed a uniform anti-ultraviolet performance, and effectively improved the final anti-ultraviolet effect of the fabric.

[0063] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A highly elastic breathable fabric, characterized in that: The high elastic breathable fabric is prepared by spinning fluorinated polymer and modified nano titanium dioxide to obtain fluorinated fibers, and finally by a blending process.

2. A highly elastic breathable fabric according to claim 1, characterized in that: The fluorinated polymer is prepared by esterification reaction of 2,2-difluoro-1,3-propylene glycol and terephthalic acid.

3. A highly elastic breathable fabric according to claim 1, characterized in that: The modified nano titanium dioxide is prepared by coating and modifying the nano titanium dioxide with chitosan.

4. The highly elastic breathable fabric according to claim 1, characterized in that: The blending process uses fluorinated fiber, cotton and nylon.

5. A method for preparing a highly elastic breathable fabric, characterized in that: The method comprises the following preparation steps: (1) Add terephthalic acid, 2,2-difluoro-1,3-propanediol, and tetrabutyltitanium bromide to dimethyl sulfoxide, place in a reaction kettle, stir at 30-40° C., 50-150 r / min for 0.5-2 h, transfer the reactants into a reaction kettle, stir at 0.08-0.12 MPa, 200-250° C., nitrogen atmosphere, at a stirring rate of 100-200 r / min, continue stirring for 1-4 h, continue pressurizing and heating, finally stir at 0.2-0.5 MPa, 250-270° C., at a stirring rate of 150-300 r / min for 3-6 h, cool and reduce the pressure to room temperature and pressure in a nitrogen atmosphere, and prepare a fluorinated polymer; (2) adding nano titanium dioxide with a particle size of 50 to 100 nm to distilled water, ultrasonically dispersing at a frequency of 50 to 200 kHz for 20 to 50 min to obtain solution A, stirring at a rate of 100 to 400 r / min at 30 to 50° C., adding chitosan while stirring, and continuing stirring for 30 to 60 min to obtain solution B, stirring at a rate of 200 to 400 r / min at 60 to 120° C. under a nitrogen atmosphere for 1 to 2 h, adding propylene oxide while stirring, reacting in a water bath at 60 to 80° C. for 4 to 8 h, cooling to room temperature after the reaction is completed, centrifuging at 4000 to 7000 rpm for 10 to 50 min, filtering to obtain a solid, drying at 50 to 80° C. for 2 to 4 h, and grinding the product to 100 to 200 meshes to obtain modified nano titanium dioxide; (3) drying the fluorinated polymer in a vacuum of 0.001 to 0.003 MPa at 100 to 150° C. for 4 to 8 hours, adding modified nano-titanium dioxide to the dried fluorinated polymer, and extruding the molten liquid through a nozzle with a nozzle aperture of 0.5 to 1.5 mm under high temperature, high voltage and nitrogen atmosphere to prepare a fluorinated high-elastic fiber; (4) 100-200 parts of fluorinated high elastic fiber, 300-600 parts of cotton and 200-400 parts of nylon are twisted, spun and woven to obtain a 200-400 g / m2 2 Highly elastic and breathable fluorinated polyester fabric.

6. The method for preparing a highly elastic breathable fabric according to claim 5, characterized in that: In the step (1), the mass ratio of dimethyl sulfoxide, terephthalic acid, 2,2-difluoro-1,3-propylene glycol and tetrabutyltitanium bromide is 70-150:50-80:20-40:0.5-2.

7. The method for preparing a highly elastic breathable fabric according to claim 5, characterized in that: The mass ratio of distilled water, nano-titanium dioxide, chitosan and propylene oxide in step (2) is 50-100:5-10:15-30:1-5.

8. The method for preparing a highly elastic breathable fabric according to claim 5, characterized in that: In the step (3), the mass ratio of the fluorinated polymer to the modified nano-titanium dioxide is 10-20:5-10.

9. The method for preparing a highly elastic breathable fabric according to claim 5, characterized in that: The high temperature in step (3) is 250-300°C.

10. The method for preparing a highly elastic breathable fabric according to claim 5, characterized in that: The high voltage in step (3) is 20-50 kV.

Citation Information

Patent Citations

  • Fluorine-containing polytrimethylene terephthalate (PTT) polyester polyester pre-oriented yarn (POY) fibers and preparation method thereof

    CN103469336A

  • High-strength composite non-woven fabric with antibacterial effect

    CN108914388A

  • Preparation method and application of elastic fiber

    CN115110189A

  • Production method of special-shaped and different-shrinkage blended polyester fiber

    CN115369513A

Cited By

  • Preparation method of waterproof antifouling modified polyester fiber

    CN120719414A